Temperature sensitivity of the low-moisture-content limit to negative seed longevity-moisture content relationships in hermetic storage - Ellis, R.H; Hong, T.D (Annals of botany, 2006)
BACKGROUND AND AIMS: The negative logarithmic relationship between orthodox seed longevity and moisture content in hermetic storage is subject to a low-moisture-content limit (m[subscript c]), but is m[subscript c] affected by temperature? METHODS: Red clover (Trifolium pratense) and alfalfa (Medicago sativa) seeds were stored hermetically at 12 moisture contents (2-15 %) and five temperatures (-20, 30, 40, 50 and 65 °C) for up to 14·5 years, and loss in viability was estimated. [bullet] Key Results Viability did not change during 14·5 years hermetic storage at -20 °C with moisture contents from 2·2 to 14·9 % for red clover, or 2·0 to 12·0 % for alfalfa. Negative logarithmic relationships between longevity and moisture contents >m[subscript c] were detected at 30-65 °C, with discontinuities at low moisture contents; m[subscript c] varied between 4·0 and 5·4 % (red clover) or 4·2 and 5·5 % (alfalfa), depending upon storage temperature. Within the ranges investigated, a reduction in moisture content below m[subscript c] at any one temperature had no effect on longevity. Estimates of m[subscript c] were greater the cooler the temperature, the relationship (P < 0·01) being curvilinear. Above m[subscript c], the estimates of C[subscript H] and C[subscript Q] (i.e. the temperature term of the seed viability equation) did not differ (P > 0·10) between species, whereas those of K[subscript E] and C[subscript W] did (P < 0·001). CONCLUSIONS: The low-moisture-content limit to negative logarithmic relationships between seed longevity and moisture content in hermetic storage increased the cooler the storage temperature, by approx. 1·5 % over 35 °C (4·0-4·2 % at 65 °C to 5·4-5·5 % at 30-40 °C) in these species. Further reduction in moisture content was not damaging. The variation in m[subscript c] implies greater sensitivity of longevity to temperature above, compared with below, m[subscript c]. This was confirmed (P < 0·005).